Clinical, biochemical and molecular analysis of two infants with familial chylomicronemia syndrome. Issue 1 (December 2016) - Zhang, Yonghong; Zhou, Jing; Zheng, Wenxin; Lan, Zhangzhang; Huang, Zhiwei; Yang, Qingnan; Liu, Chengbo; Gao, Rui; Zhang, Yongjun
Abstract Familial chylomicronemia syndrome (FCS) is a rare autosomal recessive disease due mainly to inherited deficiencies in the proteins or enzymes involved in the clearance of triglycerides from circulation. It usually happens in late childhood and adolescence, which can have serious consequences if misdiagnosed or untreated. In the present study, we investigated two Chinese male babies (A and B), 30d and 48d in age, respectively, who have milky plasma. Clinical, biochemical, and radiological assessments were performed, while samples from the patients were referred for molecular diagnosis, including genetic testing and subsequent analysis of related genes. The fasting serum lipids of the two patients showed extreme lipid abnormalities. Through a low-lipid formula diet including skimmed milk and dietary advice, their plasma lipid levels were significantly lower and more stable at the time of hospital discharge. The genetic testing revealed compound heterozygote mutations in the lipoprotein lipase (LPL) gene for patient A and two known compound heterozygote LPL gene mutations for the patient B. FCS is the most dramatic example of severe hypertriglyceridemia. Early diagnosis and timely dietary intervention is very important for affected children.